2019
DOI: 10.3390/healthcare8010006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sleep Deprivation on Blood Glucose, Food Cravings, and Affect in a Non-Diabetic: An N-of-1 Randomized Pilot Study

Abstract: Sleep deprivation is a prevalent and rising health concern, one with known effects on blood glucose (BG) levels, mood, and calorie consumption. However, the mechanisms by which sleep deprivation affects calorie consumption (e.g., measured via self-reported types of craved food) are unclear, and may be highly idiographic (i.e., individual-specific). Single-case or “n-of-1” randomized trials (N1RT) are useful in exploring such effects by exposing each subject to both sleep deprivation and baseline conditions, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
(42 reference statements)
1
12
0
Order By: Relevance
“…In our study, all respondents were recruited from the CNHHS, a survey covered 31 provinces, autonomous regions and province-level municipality in China, which can provide more information for the understanding of this area. In our study, consistent with previous findings, girls, older children, and rural children had lower risk of overweight and obesity [30][31][32]. Children doing leisure exercise were found to have a higher rate of overweight and obesity than those without leisure exercise in the current study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, all respondents were recruited from the CNHHS, a survey covered 31 provinces, autonomous regions and province-level municipality in China, which can provide more information for the understanding of this area. In our study, consistent with previous findings, girls, older children, and rural children had lower risk of overweight and obesity [30][31][32]. Children doing leisure exercise were found to have a higher rate of overweight and obesity than those without leisure exercise in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…With the increase of sleep duration, the risk of overweight and obesity gradually decreased. In terms of how sleep deprivation affects weight, Data et al [31] found the positive relationships between sleep…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants completed three-weeks of lightbox-delivered bright white light or sham for 30 minutes each morning for 12 weeks and recorded their daily depressive symptoms using a smartphone application that was specially designed for the study. Daza, Wac and Oppezzo [ 2 ] used a “self-study” N-of-1 trial design to explore the effects of sleep deprivation on blood glucose, food cravings, and affect in non-diabetic adults. In this study, two of the authors were study participants and provided measurements of activity, sleep, glucose and other outcomes via a continuous glucose meter, fitness tracker, and web-based surveys.…”
Section: Applications To New Health Conditions and Interventionsmentioning
confidence: 99%
“…Blood glucose monitoring [47] is vital for diabetic patients, as they have high glucose levels over an extended period of time. This monitoring indicates the pattern of glucose level present in an individual's blood, which helps in deciding meal plans, medications, and physical activities.…”
Section: Blood Glucose Testingmentioning
confidence: 99%